The family Opilioacaridae (Parasitiformes: Opilioacarida) in Mexico, description of two new species and notes on biology and geographical distribution - Vázquez, Ma. Magdalena; Klompen, Hans (Zootaxa, 2015)
Two new species of Opilioacaridae from Mexico are described, Neocarus chactemalensis sp. nov. and N. comalensis sp. nov., and new records for N. texanus Chamberlin & Mulaik and N. veracruzensis Vazquez & Klompen are presented. Relative positions of internal structures of the ovipositor, a highly variable character, are described based on comparisons of invaginated and evaginated ovipositors. A study of records of Opilioacaridae in Mexico shows that the group is distributed across a wide range of ecosystems and elevations, from dry, semi-desert to wet tropical forest, and coastal plains to the altiplano (>2,000m).